Association between vaping and health outcomes in patients with opioid use disorder: a systematic review protocol. Issue 1 (19th January 2021) - Sanger, Nitika; D'Elia, Alessia; Sanger, Stephanie; Rosic, Tea; Samaan, M Constantine; Kapczinski, Flávio; de Souza, Russell J; Thabane, Lehana; Samaan, Zainab
Abstract : Introduction: Vaping behaviour has increased in popularity and is particularly important to examine how it effects health outcomes in vulnerable populations, including those with opioid use disorder (OUD). With polysubstance use including cigarette and cannabis use being highly prevalent in the OUD population and cannabis/nicotine increasingly being consumed by vaping, vaping may have an important contribution to health outcomes in these individuals. The primary objective of this review is to systematically assess the literature related to patients with OUD and the effects vaping has shown on their physical and mental health. Method and analysis: A systematic search of databases including MEDLINE, Embase, PsycINFO, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, Cochrane Clinical Trials Registry, the National Institutes for Health Clinical Trials Registry and the WHO International Clinical Trials Registry Platform from inception to 31 December 2020 will be conducted. Identified citations will be screened by two reviewers to determine eligibility at the title and abstract level, and then at the full text and data extraction phases. Any disagreements in inclusion will be resolved through unblinded discussion by these reviewers, with any remaining disagreements being resolved by a third reviewer. Data collection from eligible studies will be conducted according to the data extraction form tested prior to abstraction. Included studies will be examined for quality and bias and will be meta-analysed where applicable. This protocol is reported in keeping with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines. Ethics and dissemination: The results for this review will be disseminated through publications in peer-reviewed journals, posters and presentations at scientific conferences. Additionally, we are collaborating with the Canadian Addiction Treatment Centre clinics to help disseminate the findings for this review. As this is a systematic review, no ethics approval is needed. Review registration number: CRD42020178441.